STRESS AND ITS CAUSES AND STUDY - Ravshanov Sherzod Taxirovich (Bright Mind Publishing, 2025)
The article discusses stress and its application in psychology, views on emotional experiences, feelings, types of stress and its causes.
Keywords: Stress, feeling, world, emotion, science, era, life, situation, problem, state, level, assessment.